Leisure Time Habits of BEd Students in Sagaing University of Education - Yar Zar Chit (CV. Literasi Indonesia, 2021)
This study investigated the leisure time habits of BEd students from Sagaing University of Education in Myanmar. A total of 400BEd students in Sagaing University of Education participated in this study. Descriptive research design and survey method were used. “Leisure time: activities and satisfaction” section from “ISSP 2007 Leisure Time and Sports Questionnaire” was adapted and used to collect the required data. Findings from questionnaire surveys revealed that students commonly used their leisure time for relaxation and entertainment (67.25%). It was also found that there was a significant difference in students’ leisure time habits by gender at =0.01 level. Moreover, by four habits, male students used more leisure times for physical, emotional, and social activities because their mean values are significantly different at =0.01 level. In the total mean scores, since second-year students’ mean scores are highest, they used mostly their leisure times among students (Mean=37.38). The mean and percentage of “to relax” are 2.82 and 16.40% and so it is highest among reasons. Moreover, the mean and percentage of “lack of time due to school” are 1.76 and 14.75% and so it is highest among limitations. This study hopes to give some ideas to support students’ leisure activities.